The Effect of Mineralizers on Pigmentary Properties of Cassiterite Pigments Doped by Manganese Ions - Karolová, Lucie; Dohnalová, Žaneta (Česká společnost průmyslové chemie, 2017)
The ceramic pigments of formula Sn0.752Co0.08P0.16Mn0.008O2 were prepared by classical ceramic method. The selected mineralizers were used in amount of 5 wt. % at the preparation of pigments.The synthesised pigments were applied into the organic matrix and they were evaluated from standpoint of their colour properties.
Vliv mineralizátorů na pigmentově-aplikační vlastnosti kasiteritových pigmentů dopovaných ionty manganu
Keywords: SnO2; Mineralizers; Colour properties; Particle size distribution; SnO2; mineralizátory; barvené vlastnosti; distribuce velikosti částic